ECONOMIC POLICY IN CENTRAL-EASTERN EUROPE: UNIT ROOT CONSEQUENCES - Lukas Mazal; Kevin Rowles (Acta Scientiarum Polonorum. Oeconomia, 2011)
This article aims to provide an econometric justification for economic policy in the Central and Eastern European area by examining the stability of real GDP and industrial production in the Czech Republic, Slovakia, Poland, and Hungary. Stability of GDP and industrial production is examined by unit root tests. The Dickey-Fuller (1979) unit root test indicates unit root in case of all four outputs. In case of the industrial production, the results are mixed. Nonetheless, difference stationarity of the GDP implies that there is no deterministic time trend in GDP. Therefore, there is no short-run trend reversion. Deep and long recessions are not only possible but also even likely. Thus, actions of economic policy can be regarded as justified because they are desirable to boost economy in order to reverse these recessions. This study can also be regarded as an extension of unit root tests to the post communist countries.